Temperature Control of Soft Drinks on Vehicle with Portable Storage Thermoelectric Cooler - Basri Basri; Mustofa Mustofa; Daud Patabang; Yuli Asmi Rahman; Wahyu Haryadi Piarah (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2018)
This study aims to design a control system with fuzzy logic on a system of cooling the storage of soft drinks with thermoelectric coolers. This storage can be carried in a vehicle using a DC electric power from a photovoltaic solar cell mounted on the roof of the car. Under certain conditions the energy source of cigarette lighter in a car can replace the solar cells. The test results show that a temperature of 15oC can be reached within 30 minutes with fuzzy control, while without fuzzy control the time needed in 63 minutes, 30 minutes longer.